Diseño de base de datos - Ríos Zertuche, Daniel (My University, 1985)
Abstract. We distinguish the activity of writing large programs from that of writing small ones. by large programs we mean systems consisting of many small programs (modules), possibly written by diferent people.
Keywords: modelos de datos; síntesis de atributos; formulación de esquema; métodos de acceso; seguridad e integridad